REVIEW OF CUSTOMER EXPERIENCE, PERCEIVED EFFECTIVENESS OF E-COMMERCE INSTITUTIONAL MECHANISMS, AND REPURCHASE INTENTION FROM THE PERSPECTIVE OF EXPECTATION-CONFIRMATION THEORY - Pakarti, Piji; Dharmmesta, Basu Swastha; Nugroho, Sahid Susilo; Sutikno, Bayu (Jurnal Aplikasi Manajemen, 2022)
This study aims to determine how the influence of customer experience dimensions includes functionality factors and psychological factors on e-satisfaction, trust in sellers, and repurchase intentions by involving the perceived effectiveness of e-commerce institutional mechanisms (PEEIM). The sampling technique used purposive sampling with two research objects in Yogyakarta and Semarang. The number of samples is 208 respondents. Data was collected using a questionnaire instrument distributed online and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results showed that the variables of usability, communication, trust in the seller, and context familiarity had a positive effect on e-satisfaction. Social presence, product presence, interactivity, and value for money do not affect e-satisfaction. PEEIM positively affects trust in the seller. e-satisfaction directly or indirectly affects repurchase intentions. Further research is directed to develop a research model with a more detailed object focus to get a more comprehensive understanding, for example, by comparing the types of experience products and search products.